Effectiveness of induction chemotherapy in the treatment of head and neck cancer in the San Juan de Dios hospital of the year 2010 to 2013. - Fernández Barrantes, Cristina (2018)
to evaluate the effectiveness of induction chemotherapy in the treatment of head and neck cancer in Hospital San Juan de Dios from 2010 to 2013. Methods: Clinical records of patients diagnosed with head and neck cancer and treated from 2010 to 2014 were retrospectively analyzed. Demographic, clinical and treatment information was analyzed. Progression free survival and survival rates were calculated using Kaplan-Meier plots. The median follow-up for the 33 patients was 20 months. Of the total patients included in the study, 7 patients (21%) were treated with induction chemotherapy, while 26 patients (79%) received chemoradiotherapy as a definitive treatment. Conclusion: The response at 6 months reflects a complete response of 79% in both groups; however, there is no statistically significant difference in the survival of patients with induction therapy compared to those who did not receive this treatment.